The Role of Incubators in Promoting Innovation Ambidexterity Among Start-Ups in the Tourism and Hospitality Industry - Álvaro DIAS; Carolina CAMAL; Bruno SOUSA; Leandro PEREIRA (Tourism and Hospitality Management)
Purpose - This study investigates the impact of incubators on knowledge management and sustainable innovation in early-stage tourism and hospitality firms. It explores whether incubators leverage innovation generated by these firms. Methodology/Design/Approach - Survey data from early-stage tourism and hospitality firms were analyzed using latent variable modeling and Importance-Performance Matrix Analysis (IPMA). Findings - The study reveals that incubators directly influence innovation exploitation but not innovation exploration. However, an indirect influence on exploration exists through human capital as a mediator. Originality - This research advances understanding of the relationship between knowledge management and sustainable innovation in the tourism context. It pioneers the exploration of the incubator effect on innovation ambidexterity (simultaneous pursuit of exploration and exploitation) in early-stage tourism and hospitality firms.